Strategic Teacher Development for Integrated Qur’anic Learning in Islamic Elementary Schools: Pengembangan Guru Strategis untuk Pembelajaran Al-Qur'an Terpadu di Sekolah Dasar Islam - Romli, Imam; Fahyuni, Eni Fariyatul (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Islamic education plays a central role in shaping students’ religious character through the integration of faith-based values within formal schooling. Specific Background: SD Integral Luqman Al Hakim Situbondo implements learning that combines general subjects with tauhid content, worship habituation, and Qur’anic programs (tahsin–tahfidz), yet disparities in teacher competence limit consistent implementation. Knowledge Gap: Limited studies describe structured strategic planning for improving teacher quality to support integrated Qur’anic learning at the elementary level. Aim: This study describes strategic efforts to improve teacher human resources to align instructional practices with the school’s Islamic vision. Results: Findings show the need for systematic planning through team formation, performance review, continuous training in tauhid-based pedagogy, collaboration with Qur’anic institutions, and academic supervision to standardize tahsin competence and instructional integration. Novelty: The study presents a practical strategic framework linking human resource development with integrated Qur’anic character education in elementary settings. Implications: Schools can adopt structured teacher development programs to ensure consistent integration of Islamic values, curriculum, and graduate competencies. Highlights: Strategic planning connects teacher quality with Qur’anic character formation. Tahsin standardization becomes a core component of teacher competence. Team-based management supports sustainable Islamic instructional practices. Keywords: Islamic Education, Teacher Development, Qur’anic Learning, Elementary School, Tahsin Tahfidz